The Relationship Between Abstract And Figurative Painting In Contemporary Indonesian Art In A New Way - Siklódi, Fruzsina Erzsébet (Institut Seni Indonesia Yogyakarta, 2022)
In my article, I will dissect the problem of the relationship between abstract and figurative painting in contemporary Indonesian art in a new Hungarian approach and position. The article is based on my own experience, research and studies, in which I will discuss the Hungarian parallels that I noticed during my time in Indonesia. The research refers to personal experiences gained by visiting the fine art galleries seen in Yogyakarta. The aforementioned and seen galleries and the works of art seen there will be presented. As a main element, the importance of discovering the Hungarian-Indonesian relationship examined in contemporary art appears, and we can also delve into the differences in the detail of abstract painting, figurative painting. This abstract-figurative relationship will be examined both in the Hungarian contemporary art aspect and in the Indonesian contemporary art aspect. The gesture management, color analysis and surface treatment of abstract painting are contrasted and examined with the detail, space management and conceptuality of figurative painting. Several different local works will be analyzed, which can be found in the galleries listed later.